Foolproof : why misinformation infects our minds and how to build immunity - Van der Linden, Sander (W.W. Norton & Company, 2024)
"From fake news to conspiracy theories, from inflammatory memes to misleading headlines, misinformation has swiftly become the defining problem of our era. The crisis threatens the integrity of our democracies, our ability to cultivate trusting relationships, even our physical and psychological well-being--yet most attempts to combat it have proven insufficient. In Foolproof, one of the world's leading experts on misinformation lays out a crucial new paradigm for understanding and defending ourselves against the worldwide infodemic"--
Keywords: Misinformation; Disinformation; Truthfulness and falsehood; Fake news; Social media : Moral and ethical aspects; disinformaatio; valeuutiset; sosiaalinen media; vaikuttaminen; leviäminen; psyykkiset vaikutukset; henkinen pahoinvointi; luottamus